Optimizing Decoy‐State Protocols for Practical Quantum Key Distribution Systems. Issue 4 (1st February 2021) - Fan‐Yuan, Guan‐Jie; Wang, Ze‐Hao; Wang, Shuang; Yin, Zhen‐Qiang; Chen, Wei; He, De‐Yong; Guo, Guang‐Can; Han, Zheng‐Fu
Abstract: The decoy‐state protocol enables quantum key distribution (QKD) systems to achieve high performance without using the single‐photon source. In the dozen years since the decoy‐state protocol has been proposed, a series of advances in scheme design, finite‐size analysis, system modelling, and parameter estimation has developed. Unfortunately, most advances are based on different starting points and lack a synthesis to figure out the optimal protocol of decoy‐state method. Here, the advances in decoy‐state method are reviewed and they are synthesized to compare the key‐rate performance of 38 decoy‐state protocols using the particle swarm optimization (PSO) algorithm. To form a guideline for practical QKD systems, the optimal decoy‐state protocols are found with the change of five system parameters (the transmission loss, the block size of postprocessing, the misalignment‐error probability, the dark‐count probability, and the afterpulse rate). It is expected that this work can answer the questions of what the actual performance is for different decoy‐state protocol in various scenarios and which decoy‐state protocol is the optimal choice for various QKD systems. Abstract : Decoy‐state protocols enable quantum key distribution (QKD) systems to achieve high performance securely. Recently, a series of advances of decoy‐state protocols in scheme design, finite‐size analysis, system modeling, and parameter estimation has developed. Here, they are reviewed and synthesized to find the optimal decoy‐state protocols with various system parameters in 38 decoy‐state protocols for forming a guideline for practical QKD systems.